ULTRASONOGRAPHIC ELECTIVE SUPEROVULATION AND ITS RESPONSES IN CROSSBRED AND ZEBU CATTLE - PATEL, D V; CHAUDHARI, N N; PATIL, S R; BHATOL, J G; BHALODIA, S D; DEVANAND, C P (The Indian Journal of Animal Reproduction, 2023)
In order to improve the total and viable embryo recovery rates, ultrasonography was used in cattle before induction of superovulation (SOV). The conventional SOV protocol followed in crossbred and indigenous donors at Sabarmati Ashe ram Gaushala was complemented by use of ultrasonography for selection of donors a day before stimulation. Donors with minimum 5 growing follicles were used for SOV. Dominant follicle (DF) if any was ablated 24 hours before SOVtreatment. Total 54 donors were programmed from April 2010 to April 2011, out of which 49 were flushed with recovery of 362 (7 .39) total embryos and 219 (4.47) viable embryo from 500 (10.20) ovulations; followed by 27 pregnancies from 114 embryo transfers. Data was analyzed for cross bred group (ablation vs non ablation) and indigenous group (ablation vs non ablation). Crossbred group with ablation showed highest average 12.26 ± 1.49 (mean± SE) ovulations, 11.29 ± 1.66 total embryos and 6.18 ± 1.20 viable embryos. Indigenous group with ablation had an average of 10.13 ± 1.62 ovulations, 6.38 ± 1.59 total embryos and 5.63 ± 1.24 viable embryos. Selection of donor using ultrasonograpghy and selective ablation of dominant follicle improved the SOV responses.